Damage Action for the Individual – Challenges for the National Courts in the Enforcement of EU Environmental Law: Remarks on the Judgment of the Court of Justice in the Case C-61/21 Ministre de la Transition Écologique (JP) .......... 79 - Baran, Mariusz (Fundamental Rights and Climate Change: Exploring New Perspectives and Corresponding Remedies, 2025)
This chapter aims at discussing the enforcement of EU legislation on the protection of ambient air quality through the principle of State liability for loss or damage caused to individuals as a result of breaches of EU law for which the State can be held responsible. The full effectiveness of EU rules would be impaired and the protection of the rights which they grant would be weakened if individuals were unable to obtain reparation when their rights are infringed by a breach of EU law for which a Member State can be held responsible. Accordingly, individuals who have suffered damage have a right to compensation if three conditions are met, namely that the rule of EU law infringed is intended to confer rights on them, that the infringement of that rule is sufficiently serious and that there is a direct causal link between that infringement and the damage suffered by those individuals. The analysis demonstrates the first requirement of non-contractual liability of Member States for infringement of EU law, namely the question as to whether the provisions of Directive 2008/50 establish rights for individuals. The purpose of the analysis is clarification of the extent to which an infringement of the limit values for the protection of ambient air quality under EU law can in fact give rise to entitlement to compensation. Finally, State liability is discussed further, i.e. conditions under which a possible infringement of Directive 2008/50 is sufficiently serious, and the proof of a direct causal link between the infringement and the damage.